Application of different activated attapulgites to purify phosphate contaminated wastewater - Gan, Fangqun; Hu, Jien; Tang, Rong; Qin, Pinzhu; Hang, Xiaoshuai (IOP conference series. Earth and environmental science, 2017)
Phosphate adsorption capabilities of different activated attapulgites were investigated. The natural attapulgites were treated by thermal activation over 120-800 °C for 2 h, and by hydrochloric acid solution from 1%-9%, respectively. The mechanisms of phosphate adsorption of these modified products were also studied through adsorption isotherms and adsorption kinetics experiments. The acid activation increased the phosphate sorption capacity and the highest phosphate sorption capacity occurred at AAT3 (attapulgite activated by 3% hydrochloric acid), while thermal activation did not have the same effect. AAT3 showed higher adsorption rate than natural attapulgite (AT). The phosphate adsorption isotherms of AT, H400 and AAT3 are fitted well with Langmuir equation in terms of R2 values. It suggested that the adsorption of phosphate on attapulgite was homogeneous multilayer adsorption. Based on R2 values, the kinetics of phosphate adsorption on these three attapulgites can be satisfactorily described by pseudo-second-order kinetic equation. Results of this study suggested that acid modified attapulgite could be potentially used as a promising adsorption media for phosphate removal.